Norms, Diplomatic Alternatives, and the Social Psychology of War Support. (February 2015) - Hoffman, Aaron M.; Agnew, Christopher R.; VanderDrift, Laura E.; Kulzick, Robert
Using experiments, we show that subjects who are asked about their support for war without being told about diplomatic strategies to deal with crises back military operations at levels consistent with people who are told that the alternatives to war are of low quality. In contrast, subjects who are told that diplomacy could work to resolve conflicts express less support for military operations. These results suggest that, in the absence of conflicting evidence, people premise their support for war on the assumption that leaders use force as a last resort. Implications for the study of success as an influence on public attitudes about US military operations are considered.